P195 Validation of the TEAM-ENTS (teamwork in endoscopy assessment module for endoscopic non-technical skills) framework. (19th June 2022) - Ravindran, Srivathsan; Healey, Chris; Coleman, Mark; Ashrafian, Hutan; Haycock, Adam; Archer, Steph; Darzi, Ara; Thomas-Gibson, Siwan
Abstract : Introduction: We previously developed a novel team-based non-technical skills framework in endoscopy known as TEAM-ENTS (Teamwork in Endoscopy Assessment Module for Endoscopic Non-Technical Skills). The aim of this study was to establish face and content validity of the tool. Methods: A multidisciplinary group of independent endoscopists, nurses, screening practitioners and trainees were recruited to refine items of the framework in a modified Delphi process. Items from the framework were presented as elements (subsets of overriding categories) and behavioural descriptors. An online voting platform was used with personalised links to vote anonymously. Panel members rated items against a 4-point Likert Scale and were able to leave free text comments. The item content validity index (I-CVI) was calculated based on the proportion of participants who provided a rating of 'quite or very relevant'. A result of >0.79 indicated acceptance. Participants also provided comments to guide refinement of items across rounds. Overall, two rounds were conducted, each over the space of two weeks. Results: In total, 58 participants from the UK and Ireland were recruited. There were 24 consultant endoscopists (41%), 14 clinical/nurse endoscopists (24%), 11 nurses (19%; including manager and screening practitioner roles) and 9 trainee endoscopists (16%). Median duration of experience in role was 14 years (IQR 7.75 – 20). There was a 5% attrition rate between rounds. In the first round, 9 elements and 37 behavioural descriptors did not meet consensus (I-CVI < 0.79). In total, 36 items were adjusted, 7 items were merged and 3 items were deleted. Remaining items met consensus thresholds after the second round (I-CVI > 0.79). The refined TEAM-ENTS now consists of 5 categories, 16 elements and 47 behavioural descriptors ( Figure 1 ). Conclusions: The TEAM-ENTS framework has been validated by a multidisciplinary group to reflect the core non-technical skills and behaviours relevant to endoscopy teams. This can now be implemented in team training initiatives.